Separation of allelopathy from resource competition using rice/barnyardgrass mixed-cultures. - Hai Bin He; Hai Bin Wang; Chang Xun Fang; Zhi Hua Lin; Zheng Ming Yu; Wen Xiong Lin (PLoS ONE)
Plant-plant interference is the combined effect of allelopathy, resource competition, and many other factors. Separating allelopathy from resource competition is almost impossible in natural systems but it is important to evaluate the relative contribution of each of the two mechanisms on plant interference. Research on allelopathy in natural and cultivated plant communities has been hindered in the absence of a reliable method that can separate allelopathic effect from resource competition. In this paper, the interactions between allelopathic rice accession PI312777, non-allelopathic rice accession Lemont and barnyardgrass were explored respectively by using a target (rice)-neighbor (barnyardgrass) mixed-culture in hydroponic system. The relative competitive intensity (RCI), the relative neighbor effect (RNE) and the competitive ratio (CR) were used to quantify the intensity of competition between each of the two different potentially allelopathic rice accessions and barnyardgrass. Use of hydroponic culture system enabled us to exclude any uncontrolled factors that might operate in the soil and we were able to separate allelopathy from resource competition between each rice accession and barnyardgrass. The RCI and RNE values showed that the plant-plant interaction was positive (facilitation) for PI312777 but that was negative (competition) for Lemont and barnyardgrass in rice/barnyardgrass mixed-cultures. The CR values showed that one PI312777 plant was more competitive than 2 barnyardgrass plants. The allelopathic effects of PI312777 were much more intense than the resource competition in rice/barnyardgrass mixed cultures. The reverse was true for Lemont. These results demonstrate that the allelopathic effect of PI312777 was predominant in rice/barnyardgrass mixed-cultures. The most significant result of our study is the discovery of an experimental design, target-neighbor mixed-culture in combination with competition indices, can successfully separate allelopathic effects from competition.